Influence of intellectual capital and individual absorptive capacity on innovation performance - Agostineto, Raquel Crestani; Soares, Thiago Coelho; Mazon, Gisele; Soares, Sandro Vieira (Revista de Administração da UFSM, 2022)
Purpose: The objective of this research was to identify the existence of a relationship between intellectual capital, individual absorptive capacity and the innovation performance of the Federal Institute of Santa Catarina’s technical-administrative civil servants. Methodology: Self-administered questionnaires were used as a data collection instrument, applied to the institution's technical-administrative staff, resulting in a sample of 314 respondents. In the data analysis, structural equation modeling was used. The final quantitative analysis structure resulted in 28 variables, distributed among the constructs proposed by the research. Relevance: the relevance of the study lies in the fact that individuals play a role in the creation, transfer and absorption of knowledge, thus factors at the individual level represent an antecedent for performance; therefore, at the time when the codification of knowledge occurs or expands, through assimilation, acquisition, transformation and application, a direct contribution to increasing organizational effectiveness also occurs. Results: The results showed that human capital, structural capital and relational capital influence the individual absorptive capacity, from the perspective of the institution's technical-administrative staff, with the most relevant relationship being that of human capital. Originality/Theoretical contribution: The responses indicated that the innovation performance – analyzed based on the creation and implementation of ideas – is influenced by the individual absorptive capacity. Therefore, through the results obtained, contributions to management were proposed that could contribute to the influence between the constructs, and consequently, to the individual and organizational performance.